How to clean a hippopotamus : a look at unusual animal partnerships - Jenkins, Steve, 1952-; Page, Robin, 1957- (Boston : Houghton Mifflin Books for Children, 2010)
A series of illustrations describing some of the most unusual relationships between various animals in the wild.
Notable/Best Books (A.L.A.)
School Library Journal starred
Wilson's Children
Book Links (A.L.A.), January 2011
Booklist starred, March 2010
Bulletin (Center for Children's books), June 2010
Keywords: Animal communication -- Juvenile literature; Social behavior in animals -- Juvenile literature; Animal communication; Social behavior in animals; Animal behavior; Animal communication